S-Phase Kinase-Associated Protein-2 and Nuclear Factor-kappa Beta as Molecular Targets of Oral Burkitt’s Lymphoma Cell Induced by Quinolinone Derivate-Vesnarinone - Supriatno (Current Signal Transduction Therapy, 2020)
Background: 3,4-Dihydro-6-[4-3,4-dimethoxybenzoyl-1-piperazinyl]-2(1H)-quinolinone (vesnarinone), a novel inotropic drug with unique and complex mechanisms of action, is known to show antitumor activity against several human malignancies. In the present study, vesnarinone-induced signal transduction of S-phase kinase-associated protein 2 (Skp2) and Nuclear Factor-kappa Beta (NF-ΚB) as molecular targets of oral malignant Burkitt’s lymphoma (Raji cells) was evaluated. Materials and Methods: Raji cells were incubated with vesnarinone at concentrations of 0, 1.25x10-2, 2.50x10-2, or 5.0x10-2 Molar. After 24 h, chemotactic cell migration was examined by a Boyden chamber kit. Apoptosis induction was observed by caspase-9 colorimetric assay. To evaluate levels of Skp2, NF-kB, and α-tubulin, Western blot analysis was performed. Results: Vesnarinone markedly suppressed chemotactic cell migration and significantly induced apoptosis by increasing the caspase-9 activity of Raji cells through down regulation of Skp2 and NF-ΚB. Conclusion: Vesnarinone decreased the expression of Skp2 and NF-ΚB indicating these molecules may be targeted for the treatment of oral malignant Burkitt’s lymphoma (BL). The results of this work offer a promising therapeutic approach for BL tumors.
Keywords: Burkitt' s lymphoma cell